Vibrational spectroscopic studies of hydrogen‒bonded complexes between 2, 5-dihydroxy-P-benzoquinone and amines. Issue 1 (2001) - Habeeb Habeeb, MoustafaM. MoustafaM.; Al-Wakil Al-Wakil, Hoda A. Hoda A.; El-Dissouky El-Dissouky, Aly Aly; Refat Refat, Nesrine M. Nesrine M.
Abstract : A series of 1 :1 hydrogen-bonded complexes between 2, 5-dihydroxy-P-benzoquinone (DHBQ) and various nitrogen bases of different strengths were prepared. The FT-IR spectra of the prepared complexes were examined in different regions. It has been found that the protonic and carbonyl vibrations are strongly affected by protonation. The intensity of protonic vibrations was estimated, the base line was corrected by using Perkin-Elmer Paragon 1000 program. A maximum was found at pKa = 5.6 in the correlation between the intensity and pKa (amines) suggesting a critical behavior. The same value was located as a deep minimum in the correlation between the center of gravity of the protonic vibrations, vcg cm −1, and the pKa of the amines confirming the critical behavior in some of the studied complexes. The effect of the contribution of the second OH group to the IR absorption profile was discussed. Finally, the FT-IR spectra of some deuterated complexes were presented and analysed.